2017
DOI: 10.1016/j.healun.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Incremental shuttle walk test distance and autonomic dysfunction predict survival in pulmonary arterial hypertension

Abstract: In patients with PAH, the ISWT is simple to perform, allows assessment of maximal exercise capacity, is sensitive to treatment effect, predicts outcome, and has no ceiling effect. Also, measures of autonomic function made post-exercise predict survival in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…; Billings et al . ). It is possible that the carotid chemoreceptors also play a role in the post‐exercise cardiac autonomic control in patients with more advanced disease and hypoxaemia during exercise, but it is uncertain whether the magnitude of such a phenomenon would be similar to the data reported in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…; Billings et al . ). It is possible that the carotid chemoreceptors also play a role in the post‐exercise cardiac autonomic control in patients with more advanced disease and hypoxaemia during exercise, but it is uncertain whether the magnitude of such a phenomenon would be similar to the data reported in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, this finding was valid only in patients with severe PH. In addition, a study from Sheffield (UK) analysing the shuttle walk test found that an inadequate heart rate response was associated with mortality [73]. They concluded that the shuttle walk test was easy to perform and sensitive to the effects of therapy.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The ISWT will be performed as per European Respiratory Society (ERS)/American Thoracic Society (ATS) guidelines [17]. The externally paced ISWT is a simple assessment of maximal exercise capacity and, in PH, is sensitive to treatment effect, predicts mortality, and has no ceiling effect [31].…”
Section: Primary Outcomementioning
confidence: 99%